An Empirical Investigation of Financial Performance to Corporate Governance of Indonesian Listed Banks - Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 11 No.1, 2012 JBE UNKLAB, 2012)
The objective of this study was to investigate the relationship of financial performance to corporate governance of Indonesian listed banks in year 2010.  After excluding the company with negative earnings per share, there were 30 companies left for analysis.  A regression model was used in which corporate governance as dependent variable is measured by the composite of five corporate governance aspects.  A set of financial performance measures were considered as independent variables including:  Earnings per share, price to book ratio, and debt to equity ratio.  The results indicate that financial performance has no significant relationship to corporate governance using the composite index.  Financial performance relies on earnings per share in relations to board of director size and audit committee size